Method for validating CT length measurement of cracks inside solder joints. Issue 1 (1st February 2016) - Garami, Tamás; Krammer, Oliver; Harsányi, Gábor; Martinek, Péter
Abstract : Purpose: – This paper aims to develop a method to measure the length of cracks inside solder joints, which enables the validation of computed tomography (CT) crack length measurements. Design/methodology/approach: – Cracks were formed inside solder joints intentionally by aging solder joints of 0603 size resistors with thermal shock (TS) test (−40 to +140°C, 2, 000 cycles), and CT images were captured about them with different rotational increment (1/4, 1/2 and 1°) of sample projection. The length of cracks was also measured with our method, which is based on capturing high-resolution radiography X-ray images about the cracks in two perpendicular projection planes. The radiography results were compared to the CT measurements. The percentage error for the different CT rotational increment settings was calculated, and the optimal CT settings have been determined. Findings: – The results have proven that reducing the rotational increment increases the sharpness of the captured images and the accuracy of crack length measurements. Nevertheless, the accuracy compared to high-resolution radiography measurements is only slightly better at 1/4° rotational increment than in the case of 1/2° rotational increment. It should be also noted that the 1/4° increment requires twice as much time for capturing the images as the 1/2° increment. So, the 1/2° rotational increment of sample projection is the optimal setting in our investigated case for measuring crack lengths. Practical implications: – The developed method is applicable to find the optimal settings for CT crack length measurements, which provides faster analysation of large quantity samples used, e.g. at life-time tests. Originality/value: – There is a lack of information in the literature regarding the optimisation of CT measurement set-up, e.g. a slightly larger value of the sample rotational increment can provide acceptable resolution with much faster processing time. Thus, the authors developed a method and performed research about optimising CT measurement parameters.